"ONE MUST PUMP OUT EXCESS FUNDS FROM VILLAGE USING LAWS": BOLSHEVIKS' COURSE FOR NON-MARKET RELATIONS IN SIBERIA (RUSSIA) IN 1925-1929 - Baksheev, Andrei; Novikov, Pavel; Safronov, Sergey; Koreneva, Vera; Mongush, Alla; Rakhinskiy1, Dmitriy (Revista Inclusiones, 2020)
The article provides an analysis of a prominent page in the history of the Siberian region of Russia – the Bolsheviks' grain collection policy in the late 1920s. The purpose of the study: the analysis of the essence, causes and consequences of the Bolsheviks' grain collection policy in the late 1920s. Through the use of a set of scientific methods, the authors study the grain collection policy in the late 1920s, the legislation and the Soviet government's actions regarding grain collection in the studied period, the Soviet government's return to the equivalent of the "military communism" policy, i.e. repressive measures to meet the continuously increasing grain production target. The authors conclude that the Soviet government's transition to a repressive grain collection policy in rural areas is connected not only to the needs for industrialization. The requisition of grain is also politically motivated: a radical disruption of the economic system and complete collectivization resulting in the formation of fully subordinate kolkhoz workers.